2018
DOI: 10.1042/bsr20171432
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR-155 attenuates abdominal aortic aneurysm in mice by regulating macrophage-mediated inflammation

Abstract: The aim of the present study was to identify abdominal aortic aneurysms (AAA)-associated miR-155 contributing to AAA pathology by regulating macrophage-mediated inflammation. Angiotensin II (AngII)–infused apolipoprotein E-deficient (ApoE-/-) mice and THP-1 cells model of miR-155 overexpression and deficiency were used in the experiments. The expression of miR-155 was detected by quantitative reverse transcription polymerase chain reaction (qRT-PCR). Cytokines were evaluated using enzyme-linked immunoabsorbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…Studies have shown that miR-155 plays a crucial role in rheumatoid arthritis and osteoarthritis (23). Inhibition of miR-155 attenuated the development of an abdominal aortic aneurysm by regulating macrophage inflammation (24). The paracrine activity of miR-155-enriched exosomes regulated fibroblast proliferation and inflammation in cardiac injury (22).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that miR-155 plays a crucial role in rheumatoid arthritis and osteoarthritis (23). Inhibition of miR-155 attenuated the development of an abdominal aortic aneurysm by regulating macrophage inflammation (24). The paracrine activity of miR-155-enriched exosomes regulated fibroblast proliferation and inflammation in cardiac injury (22).…”
Section: Discussionmentioning
confidence: 99%
“…8 Additionally, miR-155 has been recently reported to regulate macrophage-mediated inflammation during atherogenesis. 9 In general, miRNAs are thought to act within the cells where they are generated. However, recent studies have suggested that miRNAs are present in circulating exosomes.…”
Section: Introductionmentioning
confidence: 99%
“…A significant upregulation of miR-155-5p was identified in various cardiovascular diseases including AAA and was linked to the inflammatory response in aortic wall. It was demonstrated that expression of miR-155 correlated with inflammatory macrophage response and extracellular matrix destruction in AAA model mice [33]. On the contrary, we identified miR-155-5p as the most strongly downregulated miRNA in TAA tissue.…”
Section: Discussionmentioning
confidence: 56%
“…The distinct disease entities at the molecular level may be regulated by specific, at least partially, miRNA networks. Previous studies have demonstrated that miRNAs play key roles during the formation of AAA by dysregulating VSMC homeostasis and extracellular matrix (ECM) composition or inducing vascular inflammatory response [33,34]. However, a global high-throughput miRNA-sequencing data of TAA tissue and plasma was still missing, despite some experimental data obtained by miRNA microarrays [19,20,35].…”
Section: Discussionmentioning
confidence: 99%